The Chemical Constituents and Bioactivities of Psoralea corylifolia Linn.: A Review - Zhang, Xuenong; Zhao, Wenwen; Wang, Ying; Lu, Jinjian; Chen, Xiuping (The American journal of Chinese medicine (1979), 2016)
Psoralea corylifolia Linn. (P. corylifolia) is an important medicinal plant with thousands of years of clinical application. It has been widely used in many traditional Chinese medicine formulas for the treatment of various diseases such as leucoderma and other skin diseases, cardiovascular diseases, nephritis, osteoporosis, and cancer. Phytochemical studies indicated that coumarins, flavonoids, and meroterpenes are the main components of P. corylifolia, and most of these components are present in the seeds or fruits. The extracts and active components of P. corylifolia demonstrated multiple biological activities, including estrogenic, antitumor, anti-oxidant, antimicrobial, antidepressant, anti-inflammatory, osteoblastic, and hepatoprotective activities. This paper systematically summarized literatures on the chemical constituents and biological activities of P. corylifolia, which provided useful information for the further research and development toward this potent medicinal plant.